PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA SEOUL KOREAN RESTAURANT DI PALEMBANG - Agung Indriansyah; Sherly Malini (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2022)
This study is entitled "The Effect of Service Quality on Customer Satisfaction at Seoul Korean Restaurant in Palembang". This study aims to determine the effect of service quality on customer satisfaction at the Seoul Korean Restaurant in Palembang. The problem of this research is whether service quality has a positive effect on customer satisfaction at the Seoul Korean Restaurant in Palembang. The type of research used is descriptive of the survey method. The research sample was 60 customers, and the data collected were primary and secondary. The analysis model uses simple linear regression, correlation, coefficient of determination, and hypothesis testing using a student t-test. The results showed a positive and significant effect of service quality on customer satisfaction at the Seoul Korean Restaurant in Palembang. This shows that quality service plays an important role in shaping customer satisfaction, but it is also closely related to creating profits for the company. The higher the quality of service provided by the company, the higher the satisfaction felt by the customer.